Avaliação clínica da corticoterapia intralesional em lesão central de células gigantes dos maxilares : relevância da expressão dos receptores de corticóide e calcitonina, Cox-2, p16 e amplificação da ciclina D1 - Nogueira, Renato Luiz Maia (2010)
Central Giant Cells Lesion (CGCL) of the jaws is an intra-bone lesion with no predilection for sex and clinically divided into aggressive and non-aggressive subtypes. Histological, it shows as fibrous tissue with fusiform cells, as well as multinucleated giant cells (GC) clusters, he-morrhagic foci and neovascularization. Surgery is the regular treatment option. As new the-rapeutic approaches have been proposed, intralesional glucocorticoid injection is the main option. This paper assesses retrospectively 21 patients presenting CGCL, treated with intrale-sional triamcinolone hexacetonide by using the following protocol: intralesional injection of triamcinolone hexacetonide 20mg/mL, diluted in a solution of lidocain 2% plus epinephrine 1:200000, at a 1:1 proportion; 1mL of this final solution for each 1cm3 of lesion volume was the injected, with a total of 06 injections, one in every 15 days. Four clinical criteria were sta-bilished to evaluate treatment outcome: 1- Clinical regression or stabilization of the lesion; 2- Absence of symptoms; 3- Raising in density on radiographic controls; 4-Increased resistence when injecting the drug intralesionally. It was also performed immunohistochemical assess-ment for glucocorticoid receptor (GCR) expression, calcitonin receptor (CTR) expression, COX-2 expression, p16 expression and Ciclin D1 gene amplification by CISH, making com-parisons related to aggressivity and to therapeutic outcome. Eleven out of 21 patients of this study were women, and 10 were men. Nine of the patients had lesion located in the maxilla, 12 in the mandible. Ten patients showed aggressive lesions and 11 non-aggressive lesions. Fifteen patients showed good treatment outcome, four patients showed moderate outcome, and two patients showed negative answer to the treatment. Among the 11 patients with non-aggressive lesions, ten showed good outcome and the other, moderate outcome. Among the ten aggressive lesions, five patients showed good outcome, three patients showed moderate outcome and the remaining two patients showed negative answer to the treatment. None of them showed reicidive in a four to eight years follow-up period. Morphologic analysis found positive correlation between volume density of GC/mm2 and lesion aggressiveness, as well as significant reduction in number of GC/mm2 after treatment. Among the markers, only GCR in GC showed statistical relevance associated to the treatment. CTR was espresse in GC and in mononuclear cells in a varying way; p16 was expressed in 30% of the sample; COX-2 was not expressed at all in lesion samples and 33% of the sample showed gene amplification in Ciclin D1. None of the markers showed any statistical significant difference related to aggres-siveness nor to treatment outcome, except for GCR. The study showed the feasibility of the adopted treatment, with tendency to better outcomes in non-aggressive lesion, if compared to the aggressive ones. It also showed evidence pointing to GCR expression in GC as a reliable parameter to predict therapeutic responsiveness to glucocorticoids; and it showed that 33% of CGCL have neoplastic behaviour by Ciclin D1 gene amplification.